FINANÇAS SUSTENTÁVEIS PARA CLIENTES E SEUS FORNECEDORES: ESTUDO DE CASO DO BNDES - Martins, Anna Paula de Souza (2009)
The aim of this study was to examine measures already adopted by the Brazilian Development Bank (BNDES), in its policies and credit lines, and those that are operationally and politically feasible for the bank to adopt, in order to promote social responsibility and corporate sustainability within their lenders supply chains. It is apparent that financial tools for evaluating and granting credit that promote and assess social responsibility and corporate sustainability management and practices in lenders supply chains are still in their infancy in Brazilian financial institutions. This study is constructivist in terms of ontological aspects and phenomenological in terms of epistemological aspects. As to its purpose, the study is exploratory and in terms of means, it draws on library, document and field research through case studies. The study is based on the assumption that, within the legal framework of the financial system, financial institutions are able to influence their lenders by establishing rules, conditions and indicators for the analysis, granting and monitoring of credit. Accordingly, financial institutions power of influence may affect social responsibility and corporate sustainability practices, both within direct credit beneficiaries and their suppliers. In order to evaluate this assumption, a model was proposed an Analytical Model of Sustainability Funding Potential in the Supply Chain (SustenFor) featuring dimensions, categories and indicators that aid in assessing and monitoring the issuance of credit. These features may be included in financial institutions funding policies or products. Selecting the BNDES as the object of study, a semi-structured interview script was developed, incorporating indicators from the SustenFor Model, and the script was used to carry out individual interviews with six employees of the BNDES, all of whom work on a daily basis with activities related to social responsibility and corporate sustainability. The interviews validated 12 of the 21 indicators proposed by the model and raised some issues, particularly in terms of the lender s size and sector; these were taken on board during the model revision phase. In order to produce differentiated analysis, it is proposed that the model be applied according to sector and size of BNDES lender, to revalidate the model s dimensions, categories and indicators.